An Examination of the Gust Effect Factor for Rigid High-Rise Buildings - Liu, Yi; Kopp, Gregory A.; Chen, Shui-fu (Frontiers in Built Environment, 2021)
In order to systematically investigate the gust effect factor for rigid buildings, the derivation of the gust effect factor in ASCE 7-16 is carefully reviewed and scale model pressure tests were carried out for rectangular-plan high-rise buildings with plan aspect ratios ranging from 0.11 to 9. The gust effect factor and the aerodynamic admittance function (AAF) for area-averaged pressure coefficients and base drag coefficients were obtained and discussed in detail. The results show that the AAF has direct influence on the value of the gust effect factor, depending on whether effects of non-contemporaneous gust actions or body-generated turbulence are playing a leading role. The ASCE 7-16 gust effect factor for rigid buildings underestimates the measured values for individual walls due to differences in the AAF, peak factors, and the employment of the 3-sec moving average filter. However, the ASCE 7-16 gust factor for overall drag is estimated within 5% or better.